2019
DOI: 10.1126/sciadv.aav4620
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated polymers optically regulate the fate of endothelial colony-forming cells

Abstract: The control of stem and progenitor cell fate is emerging as a compelling urgency for regenerative medicine. Here, we propose a innovative strategy to gain optical control of endothelial colony-forming cell fate, which represents the only known truly endothelial precursor showing robust in vitro proliferation and overwhelming vessel formation in vivo. We combine conjugated polymers, used as photo-actuators, with the advantages offered by optical stimulation over current electromechanical and chemical stimulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
117
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(129 citation statements)
references
References 62 publications
(82 reference statements)
5
117
0
Order By: Relevance
“…The contribution of thermosensitive TRPV1 and TRPV4 channels to heat-induced neovascularization requires to be evaluated. This hypothesis is corroborate by the recent evidence according to which TRPV1 may integrate local heat and ROS production to stimulate ECFC proliferation and tube formation (Lodola et al, 2019). An additional facet of endothelial TRP signaling that deserves further attention is its involvement in the abnormal vascularization that features multiple diseases, such as cancer, ischemic disorders and retinal degeneration.…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…The contribution of thermosensitive TRPV1 and TRPV4 channels to heat-induced neovascularization requires to be evaluated. This hypothesis is corroborate by the recent evidence according to which TRPV1 may integrate local heat and ROS production to stimulate ECFC proliferation and tube formation (Lodola et al, 2019). An additional facet of endothelial TRP signaling that deserves further attention is its involvement in the abnormal vascularization that features multiple diseases, such as cancer, ischemic disorders and retinal degeneration.…”
Section: Resultssupporting
confidence: 76%
“…An earlier investigation confirmed that TRPV1 drove UCB-ECFC proliferation by mediating anandamide uptake in a Ca 2+ -independent manner, as also reported in EA.hy926 cells (Hofmann et al, 2014). More recently, however, Lodola et al (2019) revealed that optical excitation of PB-ECFCs with visible light (520 nm) induced TRPV1-mediated membrane depolarization when the cells were plated on the photo-sensitive polymer Poly(3-hexyl-thiophene) (P3HT). Visible light stimulation was able to promote TRPV1 opening by increasing ROS levels and local temperature within the cleft between the photo-sensitive substrate and cell surface, although a contribution of local pH was not ruled out.…”
Section: The Role Of Trpv1 and Trpv4 In Vasculogenesissupporting
confidence: 55%
See 3 more Smart Citations